Marketing social corporativo como forma de valorização de marcas : uma análise da perspectiva do consumidor - Higuchi, Agnaldo Keiti (2007)
The participation of corporations in social matters such as education, health and environment protection has been happening since many years ago. Nowadays, however, this phenomenon rises in a great rate, with an increasing number of corporations helping social causes. This phenomenon is named corporate social responsibility by ones and corporate social marketing by others. Despite this lack of consensus about the terminology, in both cases is assumed that the organization can enhance financial performance in exchange of the contribution to the social welfare, as the corporation image is reinforced by the social activities. The aim of this study is to analyze the consumer perceptions related to the social programs created by the top food industries of Paraná State witch develop corporate social marketing activities, in aspects as image enhancement, brand equity and brand consumer's preference. To accomplish this aim, the first task was to propose a conceptual definition of the corporate social marketing domains, in order to make a theoretical body consistent with this phenomenon. The next step was the empirical research, where data, collected through surveys administered by interviewer, was processed in statistic software. The results show that the consumers of the top food industries of Paraná State witch develop corporate social marketing can be divided in two groups: the skeptics, plentiful, who tend to always interpret the social action with distrust and cynicism; and the socially concerned, represented by 31,5% of the total sample, who prize the brand related to a cause. The results also show: a kind of consumer who has a positive attitude for the social actions, but due the great importance regarded to individual inner questions, don't translate it in preference in buying decision; and among the socially concerned, a share of 9,9% who argue that will stop buying the brand in case of price increase justified by the implementation of social actions.